Intraocular robotic interventional surgical system (IRISS): Semi‐automated OCT‐guided cataract removal - Chen, Cheng‐Wei; Lee, Yu‐Hsiu; Gerber, Matthew J.; Cheng, Harrison; Yang, Yan‐Chao; Govetto, Andrea; Francone, Anibal Andrés; Soatto, Stefano; Grundfest, Warren S.; Hubschman, Jean‐Pierre; Tsao, Tsu‐Chin; Clive, Loughlin (The international journal of medical robotics + computer assisted surgery, 2018)
Background With the development of laser‐assisted platforms, the outcomes of cataract surgery have been improved by automating several procedures. The cataract‐extraction step continues to be manually performed, but due to deficiencies in sensing capabilities, surgical complications such as posterior capsule rupture and incomplete cataract removal remain. Methods An optical coherence tomography (OCT) system is integrated into our intraocular robotic interventional surgical system (IRISS) robot. The OCT images are used for preoperative planning and intraoperative intervention in a series of automated procedures. Real‐time intervention allows surgeons to evaluate the progress and override the operation. Results The developed system was validated by performing lens extraction on 30 postmortem pig eyes. Complete lens extraction was achieved on 25 eyes, and “almost complete” extraction was achieved on the remainder due to an inability to image small lens particles behind the iris. No capsule rupture was found. Conclusion The IRISS successfully demonstrated semiautomated OCT‐guided lens removal with real‐time supervision and intervention.